VERTICAL JUMP OF THE ELITE MALE VOLLEYBALL PLAYERS IN RELATION THE GAME POSITION: A SYSTEMATIC REVIEW - Marques Junior, Nelson Kautzner (Revista Observatorio del Deporte, 2015)
The objective of the systematic review was of determine the vertical jump of the elite male volleyball players in relation the game position. This study followed the systematic review methodology proposed in PRISMA statement. The studies were identified in electronic databases during January of 2015 to May of 2015. Inclusion criteria of the articles were evaluated under the following search strategies: (1) type of participants, (2) type of task and (3) type of result. The studies that were excluded are the articles that were not in accordance with the inclusion criteria. The researcher selected 8 studies that were included in this systematic review. The results of the study were the following: the best squat vertical jump (SJ) were of the outside hitters/receivers (41,88±5,57 cm) and of the liberos (40±6,54 cm), the best countermovement vertical jump (CMJ) were of the opposite hitters (57,4±9,5 cm) and of the outside hitters/receivers (57,4±9,5 cm), the best countermovement vertical jump (CMJ) with arm swing were of the opposite hitters (70,67±4,55 cm) and of the outside hitters/receivers (70,67±4,55 cm). The best spike jump was of the outside hitters/receivers (80 cm) and of the opposite hitters (79,1±9,2 cm), the best block jump was of the outside hitters/receivers (60 cm) and of the setters (58 cm). However, middle blockers had the wortst spike jump and block jump, but a greater height provided a better spike reach (368 cm) and block reach (341 cm). Therefore, vertical jump and height are importants for the high performance of the elite male volleyball player.